Kniphofia foliosa Hochst, (Asphodelaceae): Medicinal Uses, Phytochemistry and Pharmacological Properties - Aladejana, Elizabeth Bosede; Musara, Collen (Journal of Pharmacy and Nutrition Sciences, 2021)
This review gives the first comprehensive appraisal of Kniphofia foliosa Hochst, from the plant family Asphodelaceae: its botany, ethnomedicinal (with particular emphasis on the African communities), phytochemistry, and pharmacological potential. Particular emphasis is given to the biological and chemical properties. Peer review and literature search were done by conducting a logical and inclusive review. Indigenous cultures have used the plant among different ethnic groups in tropical Africa for medicinal and other purposes. The chemical compounds that have been isolated from K. foliosa include monomeric anthraquinones such as chrysophanol, islandicin, laccaic acid, aloe-emodin, and aloe-emodin acetate, which contain antileukaemic properties; dimeric anthraquinones such as asphodelin, knipholone, and chryslandicin; phenyl anthraquinones and anthrones, including knipholone anthrone, isoknipholone anthrone, knipholone, phenylanthrone knipholone anthrone and anthraquinone isoknipholone; oxanthrones such as isofoliosone and foliosone; and rare dimeric phenylanthraqunones joziknipholones A and B. The pharmacological studies on K. foliosa exhibited antimalarial, antioxidant, antibacterial, anti-HIV-1, and anti-leukotriene activities. From the above, it can be deduced that K. foliosa contains chemical constituents of pharmacological importance, contributing significantly to the development of new medicines.